The EU-Azerbaijan Relations in the Gas Transporting Sector - Maksym Aliiev (Language, Culture, Politics)
The war in Ukraine changed the security landscape in Europe, the aggression of the Russian Federation also affected the energy security. For decades European elites negotiated and signed contracts for energy supplies from the Russian Federation, which gave Russia the opportunity to restore and strengthen its military capacity, and as a result, to launch an unprovoked aggression against Ukraine. Realizing the fallacy of its own energy diplomacy, the EU began searching for new and intensified relations with existing energy suppliers. The aim of this article is to analyze the role and significance of Azerbaijan as a potential supplier of gas to Europe, especially to its southern flank, where strong positions of Russian influence remain. During the preparation of the study, the international legal basis of relations between Azerbaijan and the EU was systematized and analyzed, the main supply routes of Azerbaijani gas to the European markets were determined and characterized. Prospects for deepening cooperation between the EU and Azerbaijan in the implementation of energy projects have been determined. Possible threats to the supply of Azerbaijani gas to European markets under the conditions of preservation of Russia’s influence are separately described.